Види родини Pinaceae Lindl. у дендрофлорі промислових міст степової зони України - Suslova, O.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective — to determine the species composition and to estimate vital status of plants of Pinaceae Lindl. family species in industrial cities of the Steppe zone of Ukraine. Material and methods. 4416 plants of the Pinaceae family species in decorative plantations of general use of industrial cities (Pokrovsk, Slavyansk, Avdeyivka, Konstantinovka, Khartsyzsk, Yenakiyevo, Makeyevka) were investigated. Determined species, number of individuals, their age and life condition. Viability of plants was assessed on the 8-point scale of L.S. Savelyeva, vital status — on the 5-point scale of V.A. Alexeyev. Results. In the course of our investigation, we identified seven species, three forms and one cultivar of three genera of the Pinaceae family in the examined stands. The most common tree species is Picea pungens Engelm., with representation rate of 57 % (from the total number of plants in this family) in parks, 58 % in squares and 41 % in roadside plantings. The age structure is dominated by mid dleaged trees from the age group of 21 to 30 years (47 % – in parks, 62 % – in squares, 30 % – in roadside plantings). In the city parks we revealed 90 % of healthy plants rated by high viability score, in the squares the share of such trees was 86 %, and in street plantations it was 75 %. Conclusion. Under the conditions of urban environments in the Steppe zone of Ukraine, the decrease of viability is observed in the species of Pinaceae family at the age of 40 years. The research data obtained should be taken into account when planning the reconstruction of decorative plantations and replacing the very depressed and shrinking trees of species under investigation.